A Lagrangian approach for the minimum spanning tree problem with conflicting edge pairs. Issue 1 (27th November 2020) - Carrabs, Francesco; Gaudioso, Manlio
Abstract: This article addresses the minimum spanning tree problem with conflicting edge pairs, a variant of the classical minimum spanning tree where, given a list of conflicting edges, the goal is to find the cheapest spanning tree with no edges in conflict. We adopt a Lagrangian relaxation approach together with a dual ascent and a subgradient procedure to find tight lower bounds on the optimal solution. The algorithm is also equipped with a heuristic approach which provides an upper bound by removing the conflicts from possible infeasible solutions met during the calculation of the lower bounds. The computational results, carried out on benchmark instances, show that the proposed algorithm finds the optimal solutions on several instances. Moreover, the lower bounds it provides are much more accurate than ones provided by other Lagrangian approaches available in the literature and they are computed in much less time.